Transfusion strategies in patients with cirrhosis. (19th November 2019) - Liu, Patricia; Hum, Justine; Jou, Janice; Scanlan, Richard M.; Shatzel, Joseph
Abstract: Bleeding related to portal hypertension and coagulopathy is a common complication in patients with cirrhosis. Complications and management of bleeding is a significant source of healthcare cost and utilization, as well as morbidity and mortality. Due to the scarcity of evidence surrounding transfusion strategies and hemostatic interventions in patients with cirrhosis, there has been significant debate regarding the best practice. Emerging data suggest that evidence supporting transfusion of packed red blood cells to a hemoglobin threshold of 7‐8 g/dL is strong. thrombopoietin (TPO) receptor agonists have shown promise in increasing platelet levels and reducing transfusions preprocedurally, although have not specifically been found to reduce bleeding risk. Data for viscoelastic testing (VET)‐guided transfusions appear favorable for reducing blood transfusion requirements prior to minor procedures and during orthotopic liver transplantation. Hemostatic agents such as recombinant factor VIIa, prothrombin complex concentrates, and tranexamic acid have been examined but their role in cirrhotic patients is unclear. Other areas of growing interest include balanced ratio and whole blood transfusion. In the following manuscript, we summarize the most up to date evidence for threshold‐guided, VET‐guided, balanced‐ratio, and whole blood transfusions as well as the use of hemostatic agents in cirrhotic patients to provide practice guidance to clinicians.